DEVELOPMENT OF A BIOTECHNOLOGY MODULE CONTAINING RESEARCH FINDINGS FOR BIOLOGY STUDENTS - Fauziah, Nurul; Putri, Iffa Ichwani; Nevara, Gita Addelia (Universitas PGRI Sumatera Barat, 2021)
The study aims to determine the validity of biotechnology modules containing research results for biology students. This is a design and development research project with the Plomp model development. The type of data in this study consisted of qualitative data obtained from the module validation sheet with a Likert Scale. The validation sheets in the form of questionnaires were given to the validators, who are experts on content, media, and linguistics. The aspects assessed in the validation sheets were all very valid, with values of 3.5, 3.8, 3.7, and 3.7 for content eligibility, presentation, linguistic, and graphic components, respectively. The mean score of the validity test was 3.7, which was in the category of very valid. It can be concluded that the study can be continued to the next level of the Plomp development model.